A Novel Problem-Based Learning Model Incorporating Team Teaching to Enhance Self-Determination in Nursing Students: Development and Validation - Sandra, Rhona; Firman, Firman; Razak, Abdul; Handrianto, Ciptro (Pedagogika, 2025)
This study aims to develop and validate a students’ PBL and Team-Teaching approach in order to motivate nursing students to self-directed learning during clinical practice. The study employed mixed methods and a quasi-experimental design by involving participants from four nursing schools in Indonesia. The academic and clinical perspectives support each other in enhancing students’ self-determination and clinical competence in fostering intrinsic motivation and professional growth.